Nakłady inwestycyjne na ochronę środowiska w powiecie przemyskim - Tobiasz-Salach, Renata; Bobrecka-Jamro, Dorota; Jastrzębska, Władysława (Capital Expenditure on Environment Protection in Przemyskie District, 2006)
In paper was exposed investments and expediture on enviroment protection in przemyskie district. The most importand ecological aim in przemyskie district was restrict of flue dust and fumes-, promoting of new energy carrier from recoverable sources, changing and building a new sewage- treatment plants and water intakes. The expeditures on this aim amouted 155903,5 tousand PLN (about 10% in voivodship) in 2003-2006 years.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1116, s. 734-740